Increasing the Understanding and Demonstration of Appropriate Affection in Children with Asperger Syndrome: A Pilot Trial. (24th November 2011) - Sofronoff, Kate; Eloff, Johann; Sheffield, Jeanie; Attwood, Tony
Abstract : The study was conducted to examine relationships between affectionate behavior in children with Asperger syndrome and variables likely to influence its expression (e.g., tactile sensitivity, social ability). It also evaluated the impact of a cognitive behavioral intervention that aimed to improve a child's understanding and expression of affection. Twenty-one children, aged 7 to 12 years, participated in the trial. The results showed significant correlations between measures of affection and tactile sensitivity and social ability. After attending the 5-week program, parents identified significant increases in the appropriateness of children's affectionate behavior both towards immediate family and people outside the immediate family, despite reporting no significant changes in their child's general difficulties with affectionate behavior. There was a significant improvement in children's understanding of the purpose of affection. The findings are discussed as well as the limitations of the study.